Triple Scholarly Debate: Between Father Anastas the Carmelite, As'ad Dagher, and Arbitration: Mustafa Jawad in Linguistic Criticism - Ula Fulayh Ghanim al-Sudani; Dr.Nehlah Abdullah Khalaf (Journal of College of Education, 2026)
In the context of the cultural and linguistic movement in the modern era, the Arab arena witnessed an intense scientific debate that lasted seven months, involving three prominent figures of the Arabic language: Father Anastas al-Karmali, As'ad Khalil Dagher, and Mustafa Jawad. The spark for this debate was ignited following Karmali's publication of a series of articles titled (The Errors of Earlier Linguists), in which he identified what he considered flaws in Arabic dictionaries, particularly (Muhayyat al-Muhayyat) by Butrus al-Bustani, (Aqrab al-Mawarid) by Said al-Shartuni, and (Al-Bustani) by al-Bustani, representing a result of over fifty years of work.The articles sparked a division among critics into three factions: an opposing group led by As'ad Dagher, a supportive group that took a biased judgmental stance like that of Mustafa Jawad, and a third group that sought to mediate, such as Bisher Faris. The disagreement evolved into a comprehensive linguistic debate, including exchanged written responses, the most notable of which were: (A Return to the Beginning of a Cry I Know from Akhzam) by Dagher, (The Myths and Dagherian Errors) by Karmali, and (Between Dagher, Karmali, and the Judgment of Mustafa Jawad) by Jawad, which were later collected in Karmali's book that featured his own article.Dagher's criticism focused on obliging Karmali to abide by the rules he established in his book (Tadhkirat al-Katib), enumerating what he deemed to be linguistic, syntactic, and semantic errors in his articles, including: (taṭawwur, tatwafir, bi'ya al-samad, khamsin 'am, mu'takaf, ...). Karmali responded with a lengthy debating article of about 30 pages, refuting Dagher's objections, while Jawad—acting as an arbiter—wrote a 35-page study defending most of Karmali's usages. This exchange was characterized by the depth of the discussion, sharpness of style, and boldness of critique, and was not devoid of sarcasm and insinuation.
Keywords: Debate, discussion, Al-Kirmli, As'ad Dagher, Mustafa Jawad, linguistic criticism